2017
DOI: 10.29312/remexca.v8i3.41
|View full text |Cite
|
Sign up to set email alerts
|

Eficiencia del uso de portainjerto sobre el rendimiento y dinámica nutricional foliar de macronutrientes en pimiento morrón

Abstract: ResumenEl objetivo del presente trabajo fue estudiar la eficiencia del uso de portainjerto sobre el rendimiento y dinámica nutricional foliar de macronutrientes en pimiento morrón. Se utilizaron las variedades comerciales de pimiento morrón Fascinato y Janette y el portainjerto comercial Terrano. El experimento se desarrolló en un sistema de malla sombra en Delicias, Chihuahua, México durante el ciclo de producción 2012. Los resultados indican que la combinación variedadportainjerto Fascinato-Terrano y Janette… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
1
0
0
Order By: Relevance
“…T2:P/MA achieved the highest weight (5445 g), being inside the same statistical group to treatments T4:P/CL and T3:P/MO; however, it proved superior by 99.45% than the cucumber without rootstock (T1:PSP) (Table 1). Regarding NFPP and PFPP, a major increase was found in grafted plants versus non-grafted plants, matching the observations of other research works with grafted versus non-grafted plants of bell pepper and watermelon [22][23][24]. However, other research works have reported low yields of plants that were grafted in different rootstocks, as compared to non-grafted cucumber plants [25].…”
Section: Resultssupporting
confidence: 86%
“…T2:P/MA achieved the highest weight (5445 g), being inside the same statistical group to treatments T4:P/CL and T3:P/MO; however, it proved superior by 99.45% than the cucumber without rootstock (T1:PSP) (Table 1). Regarding NFPP and PFPP, a major increase was found in grafted plants versus non-grafted plants, matching the observations of other research works with grafted versus non-grafted plants of bell pepper and watermelon [22][23][24]. However, other research works have reported low yields of plants that were grafted in different rootstocks, as compared to non-grafted cucumber plants [25].…”
Section: Resultssupporting
confidence: 86%